2016
DOI: 10.1007/s11120-016-0312-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of excitation energy transfer in cyanobacterial photosystem I in solution and immobilized on conducting glass

Abstract: Excitation energy transfer in monomeric and trimeric forms of photosystem I (PSI) from the cyanobacterium Synechocystis sp. PCC 6803 in solution or immobilized on FTO conducting glass was compared using time-resolved fluorescence. Deposition of PSI on glass preserves bi-exponential excitation decay of ~4–7 and ~21–25 ps lifetimes characteristic of PSI in solution. The faster phase was assigned in part to photochemical quenching (charge separation) of excited bulk chlorophylls and in part to energy transfer fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 13 publications
(40 citation statements)
references
References 53 publications
9
31
0
Order By: Relevance
“…Cyanobacterial PSI immobilized directly on FTO conducting glass has recently been shown by ultrafast optical spectroscopy to preserve excitation quenching properties very similar to those of the native PSI in solution (Szewczyk et al 2017(Szewczyk et al , 2018. The detailed analysis has shown that the observed modest acceleration of the excitation decay in immobilized PSI (by a few ps) may be assigned to the crowding effect similar to that reported for aggregated LHCII (Ruban et al 2007).…”
Section: Introductionmentioning
confidence: 54%
See 4 more Smart Citations
“…Cyanobacterial PSI immobilized directly on FTO conducting glass has recently been shown by ultrafast optical spectroscopy to preserve excitation quenching properties very similar to those of the native PSI in solution (Szewczyk et al 2017(Szewczyk et al , 2018. The detailed analysis has shown that the observed modest acceleration of the excitation decay in immobilized PSI (by a few ps) may be assigned to the crowding effect similar to that reported for aggregated LHCII (Ruban et al 2007).…”
Section: Introductionmentioning
confidence: 54%
“…In the following, we present photovoltaic data obtained from the system containing simple PSI-FTO photoelectrode identical to that one described in Szewczyk et al (2017Szewczyk et al ( , 2018 and propose a mechanism of the anodic and cathodic photocurrent generation in this system. The advantage of this system is the functionality of immobilized PSI proven to be highly intact at the level of excitation decay and charge separation.…”
Section: Introductionmentioning
confidence: 83%
See 3 more Smart Citations